2022
DOI: 10.5194/hess-26-3989-2022
|View full text |Cite
|
Sign up to set email alerts
|

Bedrock depth influences spatial patterns of summer baseflow, temperature and flow disconnection for mountainous headwater streams

Abstract: Abstract. In mountain headwater streams, the quality and resilience of summer cold-water habitat is generally regulated by stream discharge, longitudinal stream channel connectivity and groundwater exchange. These critical hydrologic processes are thought to be influenced by the stream corridor bedrock contact depth (sediment thickness), a parameter often inferred from sparse hillslope borehole information, piezometer refusal and remotely sensed data. To investigate how local bedrock depth might control summer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Lateral seeps and springbrooks sourced by shallow groundwater may exhibit more variable and higher temperatures over time due to climate change (Hare et al, 2021; KarisAllen et al, 2022). Perennial streams also can become intermittent during extended dry periods (Costigan et al, 2015; Gendaszek et al, 2020; Price et al, 2021), thereby disconnecting CWPs from warm stream reaches in headwater systems (Briggs et al, 2022). Cold‐water patches fully mix with ambient water at high streamflow in rivers draining large stratified natural lakes that show abrupt wind‐driven drops in river temperature, leading to the loss of discrete CWPs (Lisi & Schindler, 2015) and a reduction in CWRs.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Lateral seeps and springbrooks sourced by shallow groundwater may exhibit more variable and higher temperatures over time due to climate change (Hare et al, 2021; KarisAllen et al, 2022). Perennial streams also can become intermittent during extended dry periods (Costigan et al, 2015; Gendaszek et al, 2020; Price et al, 2021), thereby disconnecting CWPs from warm stream reaches in headwater systems (Briggs et al, 2022). Cold‐water patches fully mix with ambient water at high streamflow in rivers draining large stratified natural lakes that show abrupt wind‐driven drops in river temperature, leading to the loss of discrete CWPs (Lisi & Schindler, 2015) and a reduction in CWRs.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Interestingly, despite the clear importance of groundwater metrics in the clustering analysis, results from summary metric regressions were mixed and, in the Snoqualmie basin, did not align with expectations of a negative relationship between thermal sensitivity and groundwater influence (Table 3). Although it is possible to infer broad patterns in surface-groundwater connectivity using datasets of interpolated hydrogeologic properties (i.e., hydraulic conductivity, soil depth) or water source (i.e., baseflow index), individual hydrogeologic metrics often have substantial uncertainty, do not covary perfectly, and may be particularly unconstrained for mountain headwater streams (Wolock et al 2004, Patton et al 2018, Briggs et al 2022. Additionally, the influence of these processes can be localized and variable across space (Johnson et al 2017) and substantially impacted by human modification.…”
Section: Climate Controls On Thermal Sensitivitymentioning
confidence: 99%
“…Groundwater exchange processes have important moderating effects on stream flow and temperature (Kaandorp et al, 2019; Winter, 2007), and this affects the quality and connectivity of fish habitat (Kurylyk et al, 2014; Meisner et al, 1988). Streams flowing over shallow unconfined aquifers constrained by near‐surface bedrock exhibit more seasonal dewatering and more thermal sensitivity to air temperature than streams connected to deeper groundwater sources (Briggs et al, 2022). Moreover, a continental‐scale study demonstrated that streams dominated by shallow groundwater sources are warming in significantly greater proportion than streams fed by deeper groundwater sources, particularly over summer months (Hare et al, 2021).…”
Section: Introductionmentioning
confidence: 99%